POSTMODERNISM AND KNOWLEDGE DEVELOPMENT IN NURSING - Zardosht, Roghayeh (International Journal of Psychosocial Rehabilitation, 2020)
Postmodernism, a movement against the intellectual foundation for the eternal and universal values. Because there is no single definition of it. The postmodern historical period represents the transition from the rigid logical positivism and science is entering a new vision, a vision that includes values, conditions, and human factors. Postmodernism protests as scientific arguments began in the early twentieth century. This paper aims to investigate the role of a postmodernism in the development of nursing knowledge, has been done.In this study to find relevant sources, library studies and review the books available Databases include (CINHAL), (Proquest), (science direct), (Ovid), (Magiran), (web of science), (pub med) and available book in the faculty of nursing library were searched by keywords (postmodernism) (knowledge development), (nursing knowledge) separately and in combination in the title, abstract and keywords.Finally, a total of 19 full-length articles and 14 books,which were related to the subject of the study and published from 1990 to 2018, were used as the references for this study to explorethe role of this philosophical tradition in the development of the nursing knowledge.At the time of postmodernism, knowledge, science, and even the image of nursing, health, human health, and environment play a lot of truth itself has shown. Indeed, postmodernism for nursing truth without fences and wide, including horizontal of fusion means at: authority, ethos, ethics, communications, health care, environment, sustainability, aesthetics, structural interpretation, and cares. Many of the characteristics of postmodernism are congruent with nursing values and traditional practices. Routes of postmodernism in contemporary nursing knowledge and nursing theory as the theory of Newman, Parse, Rogers, Sartre, and Watson were seen. The transition matrix in the range of nursing science knowledge, concepts as the evolution of consciousness, higher self, open system, harmony, and communication with space - time, patterning and Holism revealed. Such thoughts staunch opposition to themes and templates prior to knowledge in nursing. Postmodernism focuses on epistemology and language, especially narratives as multiple truths, knowledge, uncertain and temporary, as the aim was to develop Nursing. Common themes of postmodernism and separate paragraph, including anti-fundamentalist, is a large discrepancy between theory and rejection of competent discourses. The main motto of postmodernism, which means “the center does not hold “we are in the center of nursing knowledge that does not be kept. We create, we can regenerate the same time build a new center, a new form of human experience and knowledge that will guide humanity towards greater emancipation and development, especially with respect to the art and science of nursing and the health care and the way of adaptation of knowledge and experience in a vast world of human health. Therefore, nurses have the knowledge to understand the impact of a change.